Лексична інтеркаляція у мові тижневика Об'єднання Українців у Польщі "Наше слово" - Харченко, І. (Культура народов Причерноморья, 2002)
The article includes the consideration of interference general concept, it’s peculiarities on the diaspora basis. The particular attention is paid to the practical analysis of lexical deflexions in the newspaper “Nashe slovo”.